Lands and peoples. The world in color. Volume 2 : Skandinavia, sentral Europe, Italy - Merrick, Helen Hynson
Norway -- Sweden -- Finland -- Iceland and Greenland -- Denmark -- Germany -- Berlin -- Poland -- Estonia, Latvia and Lithuania -- Czechoslovakia -- Austria -- Hungary -- Switzerland -- Little Europe -- Luxembourg -- Italy -- Rome -- Venice -- Sicily